Effectiveness and Timing of Trichoderma polysporum Inoculation on Controlling Fusarium wilt (Fusarium oxysporum f. sp. lycopersici (Sacc.) in Tomato Plants - Susiana Susiana (Contributions of Central Research Institute for Agriculture, 2023)
This study aims to determine the effect of the dose and application time of T. polysporum on the effectiveness of controlling Fusarium wilt in tomato plants. Fusarium wilt disease (Fusariun oxysporum) is an important disease in various cultivated plants, especially tomato plants. Fusarium wilt occurs in all tomato growing areas around the world and causes huge losses of up to 60%. Control of F. oxysporum pathogens using fungicides on agricultural land can cause environmental pollution. One of the environmentally friendly control alternatives is to use the biological agent Trichoderma polysporum. The results showed that compost containing T. polysporum was effective for controlling Fusarium wilt in tomato plants. The percentage effectiveness of compost containing T. polysporum in controlling the intensity of disease attacks, namely 0% in the control treatment, 47.80% with the application of 0.25 kg of compost containing T. polysporum, and 70.87% with the application of 0.5 kg of compost containing T. polysporum. The effect of time of application of compost containing T. polysporum is equally effective for controlling the pathogen attack of F. oxysporum. The large doses of T. polysporum compost applied prior to inoculation of the pathogen can increase plant growth and yield. In the application of 0.5 kg of compost containing T. polysporum, the highest growth in plant height was 18.03-19.84 cm, while the lowest growth average was in the control treatment of 16.53-16.70. The highest average plant production, namely 237.65 grams, was found in the application treatment 0.